2022
DOI: 10.3390/bioengineering9060239
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Human Umbilical Tissue-Derived Hydrogels Promote Proliferation and Chondrogenic Differentiation of Mesenchymal Stem Cells

Abstract: Tissue engineering is a promising approach for the repair and regeneration of cartilaginous tissue. Appropriate three-dimensional scaffolding materials that mimic cartilage are ideal for the repair of chondral defects. The emerging decellularized tissue-based scaffolds have the potential to provide essential biochemical signals and structural integrity, which mimics the natural tissue environment and directs cellular fate. Umbilical cord-derived hydrogels function as 3D scaffolding material, which support adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 79 publications
5
18
0
1
Order By: Relevance
“…According to the literature, the generation of the hydrogel network depends signi cantly on the β-sheet structure [14,41,42]. Recent ndings showed the hydrogel was found to be supportive in terms of both mechanical and biochemical properties, which is consistent with the ndings of the prior reports [22,43,44]. After being identi ed and planted into the scaffold, MSCs, in accordance with earlier scaffold research, were observed to interact in a biocompatible and migratory pattern.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…According to the literature, the generation of the hydrogel network depends signi cantly on the β-sheet structure [14,41,42]. Recent ndings showed the hydrogel was found to be supportive in terms of both mechanical and biochemical properties, which is consistent with the ndings of the prior reports [22,43,44]. After being identi ed and planted into the scaffold, MSCs, in accordance with earlier scaffold research, were observed to interact in a biocompatible and migratory pattern.…”
Section: Discussionsupporting
confidence: 83%
“…The smooth bril structures and associated open space pores were visible in the hydrogel architecture. The porous hydrogel scaffolds contained the connected open space pores and smooth lament architecture as mentioned in our previous article [22]. The results showed that the hydrogel topography was wavy, shear, tension, and indentation, with varying magnitudes and heights.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations